Austin and the Scope of Our Knowledge - Leite, Adam (International journal for the study of skepticism, 2022)
In ordinary circumstances in which we know there is a goldfinch on a branch in the garden, do we know that the thing on the branch isn’t stuffed? Austin’s methodology is perfectly compatible with holding both that we do and that we wouldn’t know it’s a goldfinch if we didn’t. Moreover, Austin’s methodology supports the claim that if we had no information whatsoever about whether it is stuffed, we wouldn’t know the thing on the branch is a goldfinch. Finally, Mark Kaplan’s claim that P is part of your evidence if and only if you know that P leaves him with good reason to agree that in ordinary circumstances, you do know that the goldfinch isn’t stuffed. This result suggests a distinctive way of approaching arguments for external world skepticism with the structure of the so-called Argument from Ignorance. And it highlights just how much can be learned from approaching epistemological issues in an Austinian spirit.